2015
DOI: 10.1007/s00395-015-0495-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial mitochondrial dysfunction in mice lacking adiponectin receptor 1

Abstract: Hypoadiponectinemia is an independent predictor of cardiovascular disease, impairs mitochondrial function in skeletal muscle, and has been linked to the pathogenesis of Type 2 diabetes. In models of Type 2 diabetes, myocardial mitochondrial function is impaired, which is improved by increasing serum adiponectin levels. We aimed to define the roles of adiponectin receptor 1 (AdipoR1) and 2 (AdipoR2) in adiponectin-evoked regulation of mitochondrial function in the heart. In isolated working hearts in mice lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…This is in accordance with previous studies that associate reduced expression of AdipoR1 in the heart muscle to intolerance of ischemic injury 35 and consequent pathologic processes 36 and that reduced activities of mitochondrial oxidative phosphorylation complexes; i.e., of AMPK, and PGC1 signaling contribute to diabetic cardiomyopathy. 37 Results of this study clearly demonstrated that AdipoRon improved high-glucose-induced oxidative stress and lipotoxicity by activating intrarenal AdipoR1/AdipoR2, which in turn activated the intracellular Ca ++ /AMPK/PPARa pathway without affecting serum adiponectin level. Human diabetic kidneys exhibit decreased AdipoR1/AdipoR2, CaMKKb, phosphorylated AMPK, phosphorylated LKB1, and nephrin expression even in the early stages of CKD and show negligible changes in relevant molecular expression with increasing stages of CKD.…”
Section: Discussionmentioning
confidence: 57%
“…This is in accordance with previous studies that associate reduced expression of AdipoR1 in the heart muscle to intolerance of ischemic injury 35 and consequent pathologic processes 36 and that reduced activities of mitochondrial oxidative phosphorylation complexes; i.e., of AMPK, and PGC1 signaling contribute to diabetic cardiomyopathy. 37 Results of this study clearly demonstrated that AdipoRon improved high-glucose-induced oxidative stress and lipotoxicity by activating intrarenal AdipoR1/AdipoR2, which in turn activated the intracellular Ca ++ /AMPK/PPARa pathway without affecting serum adiponectin level. Human diabetic kidneys exhibit decreased AdipoR1/AdipoR2, CaMKKb, phosphorylated AMPK, phosphorylated LKB1, and nephrin expression even in the early stages of CKD and show negligible changes in relevant molecular expression with increasing stages of CKD.…”
Section: Discussionmentioning
confidence: 57%
“…Adiponectin was shown to attenuate vascular and myocardial oxidative stress by inhibiting NADPH oxidase‐derived superoxide anion in mice subjected to 30 min of transient myocardial ischemia (30). Evidence of ROS‐induced decrease in mitochondrial coupling efficiency and the presence of dysfunctional oxidative phosphorylation complexes were shown in isolated hearts from AdipoR1 –/– mice (41). In light of those observations, we investigated the effect of CP‐3(iv) pretreatment in reducing NADPH‐stimulated ROS production in LV homogenates after 6 h of reperfusion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Male mice with global deficiency of AdipoR1 (Adipor1 −/− ) and respective C57BL/6J wildtype (WT) littermate controls were investigated at 8 weeks of age, as described previously (6). Mice were housed in individually-ventilated cages with 12 h daylight/dark cycles at 22 • C and were fed a laboratory standard chow and had free access to water.…”
Section: Animalsmentioning
confidence: 99%
“…Its role in regulating glucose homeostasis therefore suggests that the observed decrease in serum levels of adiponectin in non-insulin dependent (type 2) diabetes mellitus (NIDDM) is involved in the pathogenesis of insulin resistance and ultimately NIDDM (2,3). Impaired adiponectin activity has also been implicated in the development of end-organ diabetic complications including diabetic cardiomyopathy, nephropathy and non-alcoholic steatohepatitis (4)(5)(6). Maintaining or restoring intact adiponectin signaling is therefore a promising therapeutic strategy to attenuate these diabetic complications (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation